1998
DOI: 10.1139/v98-107
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of secondary structure on the α-C→H bond dissociation energy of proline residues in proteins: a theoretical study

Abstract: Ab initio computations (B3LYP/6-31G(D), coupled with isodesmic reactions) were used to predict αC→H bond dissociation energies (BDEs) for proline as a residue in a model peptide, intended to mimic the environment in proteins. The environment was further constrained to mimic common proline positions in turns of different types. The BDEs were found to be very dependent on the structural constraints imposed by the turn type, implying different structure-mediated susceptibilities to free radical damage to proline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Theoretical calculations predicted that thiyl radicals should react with α C-H bonds of most amino acids in proteins when located in flexible or β-sheet structures but not in α-helices[2427]. Our kinetic NMR experiments confirmed that inter molecular hydrogen atom transfer (HAT) reactions of the general type displayed in Scheme 1, equilibrium 2, occur between thiyl radicals and several amino acids[28].…”
Section: Introductionsupporting
confidence: 58%
“…Theoretical calculations predicted that thiyl radicals should react with α C-H bonds of most amino acids in proteins when located in flexible or β-sheet structures but not in α-helices[2427]. Our kinetic NMR experiments confirmed that inter molecular hydrogen atom transfer (HAT) reactions of the general type displayed in Scheme 1, equilibrium 2, occur between thiyl radicals and several amino acids[28].…”
Section: Introductionsupporting
confidence: 58%
“…Experimentally-determined values are shown in bold; calculated values are shown in italics. b Hydrogen-atom abstraction reaction efficiency = second-order hydrogen-atom abstraction rate constant/collision rate constant (k exp /k coll ). c Reference 71. d Reference 61. e Reference 53. f Reference 72. g Reference 62. h Reference 22. i Reference 74. j Average of the BDE values for cis- and trans- proline; reference 75. k Reference 73. …”
Section: Figures and Tablesmentioning
confidence: 99%
“…via “long range hydrogen transfer” (based on the position of amino acids within the protein sequence) (reaction 8). Theoretical calculations by Rauk and co-workers show that thiyl radicals should react with α C-H bonds of protein amino acids when located in flexible or β-sheet structures but not within α-helices [7982]. …”
Section: Hydrogen Transfer Reactions Of Thiyl Radicalsmentioning
confidence: 99%